The Correlation Between Learning Environment and Students’ Motivation in English at MAN 1 Kota Makassar - Khalisah, Nur; Korompot, Chairil Anwar; Fauzan, Muhammad Miftah (Journal of Excellence in English Language Education, 2025)
This study examines the relationship between the learning environment and students' motivation in acquiring English language skills. The study employs a quantitative correlational design, utilizing a singular instrument: a questionnaire. The study population consists of XII grade students from MAN 1 Kota Makassar, with a sample of 33 students from class XII IPA 1. Data were quantitatively gathered via a questionnaire and analyzed utilizing SPSS version 26. The data analysis findings indicate a substantial linear association between the learning environment and student motivation, evidenced by a correlation coefficient of 0.749. This signifies a modest positive association, indicating that an enhanced learning environment fosters more student motivation throughout the educational process.